Titanium implant with osteogenesis-promoting antibacterial film layer and preparation method of titanium implant
By forming a stick -shaped nanogenic structure on the surface of titanium planting and doped ions, combining antibacterial solutions to form antibacterial layers, solving the problem of lack of bone and antibacterial properties of titanium implantation, and realizing biocompatible biological compatibility of titanium implantation. Increases of sex and antibacterial ability.
Patent Information
- Application Number
- CN202411430309.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-24
AI Technical Summary
Existing titanium implants lack osteogenic and antibacterial properties in clinical applications, resulting in the possibility of sterile loosening and implant-related infections after surgery.
Form the stick-shaped nano structure on the surface of the titanium planting through water and heat reactions, and exchange ions through an ion exchange on its surface to form SRTIO3 nano-rods, and then form a layer of antibacterial properties in antibacterial solutions. The titanium planting of the membrane layer.
The bone and antibacterial properties on the surface of titanium implantation are realized, the biocompatibility and antibacterial ability of the implantation body are enhanced, and the clinical application effect is improved.
Smart Images

Figure CN119345455A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a titanium implant with an osteogenic-antibacterial functional film layer and a preparation method thereof, and belongs to the field of surface modification of biomedical metal materials. Background Art
[0002] As a metal implant, pure titanium has the advantages of low density, high strength, excellent corrosion resistance and good biocompatibility. In clinical applications, the human body environment is relatively complex, and it is difficult for the titanium alloy surface to spontaneously form a passivation film to improve its corrosion resistance. Since it does not have osteogenic and antibacterial activity, it is easy to have aseptic loosening and implant-related infection after surgery. In order to improve the problems faced, the surface of pure titanium is usually modified.
[0003] Surface modification can change one or more properties, including surface morphology, wettability and corrosion resistance, which greatly affects the in vitro and in vivo performance of implants. Existing surface modifications include acid etching, micro-arc oxidation and anodizing. Acid etching will form micro-pits and nano-nodules on the surface of the metal substrate. This nanostructure increases the surface roughness and is conducive to cell adhesion, but the use of acid agents will pollute the environment, and improper handling may cause harm to operators. Micro-arc oxidation uses high-voltage electrolysis to form a thick and dense oxide film on the surface of titanium alloy. The oxide film prepared by this method is micron-level thick. Too much thickness may increase the brittleness of the film layer, thereby affecting its mechanical properties. Anodizing is to form a protective oxide film by electrolytic oxidation, but on workpieces with complex shapes, the film layer may be formed unevenly. Therefore, a method that is both environmentally friendly and can form a film layer on workpieces with complex shapes is needed.
[0004] The chemical structure and polarity of strontium (Sr) are similar to those of calcium (Ca). Its content in bones accounts for about 0.01% of bone mass and it is an essential trace element in human bone tissue. 2+ Can act as a bone-inducing factor to replace Ca 2+ Participate in the physiological activities of bone metabolism, promote the differentiation of osteoblasts and the mineralization of bone matrix, and inhibit the growth and differentiation of osteoclasts.
[0005] Metal-organic frameworks (MOFs) are highly ordered porous materials composed of metal ions or metal clusters connected to organic ligands through coordination bonds. They have the advantages of high adjustability, large specific surface area, porosity and chemical stability. Among them, ZIF-8 is the most common type of MOF material, which is composed of zinc ions (Zn 2+) and imidazole ligands, similar to zeolite, forming a three-dimensional framework structure. With its unique structure and excellent performance, it is widely used in gas storage, separation and catalysis. In addition, it has gradually shown great application potential in the biomedical field. The nanostructure of ZIF-8 has natural antibacterial properties and can decompose and release Zn by responding to external stimuli (such as pH, temperature, magnetic field, etc.). 2+ .
[0006] In the prior art, the following documents are available on bone repair materials containing strontium zinc and rod-shaped nanostructures on the surface of titanium alloys:
[0007] Patent application number CN201210492752.5 discloses a method for preparing a strontium titanate hollow nanorod array. The method uses a zinc oxide nanorod array as a sacrificial template and combines liquid phase deposition technology to achieve simultaneous deposition of strontium titanate and consumption of zinc oxide, thereby preparing a strontium titanate hollow nanorod array. The invention is simple to operate and can be prepared on a large scale. However, the reaction solution used in the invention has certain environmental hazards, so its application is subject to certain restrictions.
[0008] Patent application number CN200880024025.8 discloses a bone tissue implant containing strontium ions and a method for preparing the same. In addition, the invention also provides a sandblasting powder containing strontium ions and a method for locally increasing bone formation. The bone tissue implant is covered with an oxide layer containing strontium ions, and the thickness of the oxide layer is within 100 nm. The invention enhances the osteogenic effect of the implant, but does not have antibacterial properties.
[0009] The patent with application number CN201810842978.0 discloses a new type of osteogenic composite bone repair material containing strontium, and its preparation method and use. The raw materials of the material include strontium-containing α-calcium sulfate hemihydrate and nano-hydroxyapatite, which are mixed in a certain proportion to form a new type of composite material. The invention retains the good biocompatibility of Sr-α-CSH and improves the material properties of the excessive degradation of pure Sr-α-CSH, giving full play to the osteogenic effect of strontium ions. However, the invention technology cannot be directly applied to titanium implants.
[0010] The patent with application number CN202010736222.5 discloses a method for preparing a TiO2 and porous carbon nanocomposite material with antibacterial properties. The method uses zinc nitrate hexahydrate, 2-methylimidazole and methanol to prepare ZIF-8 material, prepares TiO2 precursor-coated ZIF-8 composite material based on isopropyl titanate and ZIF-8 dispersion, and finally carbonizes the TiO2 precursor-coated ZIF-8 composite material at high temperature to obtain a nano-TiO2 / carbon composite material. The TiO2 prepared by this invention has enhanced photocatalytic activity and enhanced antibacterial properties of the composite material. However, the composite material prepared by this invention does not have an osteogenic effect, so its application is subject to certain restrictions. Summary of the invention
[0011] The technical problem to be solved by the present invention is: how to improve the osteogenic and antibacterial properties of the surface of titanium implants, thereby improving their clinical application effects.
[0012] In order to solve the above problems, the present invention provides a method for preparing a titanium implant with an osteogenic-antibacterial film layer: a titanium implant is subjected to a hydrothermal reaction to form a rod-shaped nanostructure on its surface; the titanium implant is then placed in an osteogenic solution, and strontium ions are doped into the nanorods through ion exchange to obtain SrTiO3 nanorods with an osteogenic coating; the SrTiO3 nanorods are placed in an antibacterial solution to form an osteogenic-antibacterial coating on the surface of the SrTiO3 nanorods, thereby obtaining a titanium implant with an osteogenic-antibacterial film layer.
[0013] Preferably, the hydrothermal reaction is carried out in a NaOH aqueous solution for 4 to 8 hours, and the reaction is rinsed and dried after completion.
[0014] More preferably, the concentration of the NaOH aqueous solution is 40 g / L.
[0015] Preferably, the osteogenic solution is an aqueous solution of (CH3COO)2Sr.
[0016] More preferably, the concentration of (CH3COO)2Sr in the osteogenic solution is 2.057-205.710 g / L, and the solvent is deionized water.
[0017] Preferably, the titanium implant is placed in an osteogenic solution at a temperature of 100° C. and kept warm for 1 hour.
[0018] Preferably, the antibacterial solution is an aqueous solution containing dimethylimidazole and Zn(NO3)2·6H2O.
[0019] More preferably, the concentration of dimethylimidazole in the antibacterial solution is 11.35 g / L, the concentration of Zn(NO3)2·6H2O is 0.55 g / L, and the solvent is deionized water.
[0020] Preferably, the SrTiO3 nanorods are placed in an antibacterial solution at a temperature of 37°C for 0.5 to 1 hour, and finally rinsed and dried.
[0021] The present invention also provides a titanium implant having an osteogenic-antibacterial film layer prepared by the preparation method.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The osteogenic-antibacterial membrane prepared by the present invention has the following advantages:
[0024] 2. The nanorods prepared by the present invention are vertically distributed on the surface of the titanium alloy, have three-dimensional spatiality, and the nanoscale size can pierce bacteria, having a physical antibacterial effect;
[0025] 3. SrTiO3 nanorods can slowly release strontium ions and have the ability to promote bone formation;
[0026] 4. ZIF-8 has a stable structure, can release zinc ions, and has natural antibacterial properties;
[0027] 5. ZIF-8 has a pH response effect and can decompose in an acidic environment, releasing a large amount of zinc ions, which has a stronger bactericidal effect;
[0028] 6. The preparation method of the osteogenic antibacterial coating of the present invention is simple and environmentally friendly, and can reduce implant processing costs and environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a morphology of apatite induced deposition of the treatment layer of the titanium alloy obtained in Example 1 after being immersed in simulated body fluid;
[0030] Figure 2 This is a flat plate image of the titanium alloy in vitro antibacterial properties obtained in Example 1;
[0031] Figure 3 This is a morphology of apatite induced deposition of the treatment layer of the titanium alloy obtained in Example 2 after being immersed in simulated body fluid;
[0032] Figure 4 This is a flat plate image of the titanium alloy in vitro antibacterial properties obtained in Example 2;
[0033] Figure 5 This is a morphology of apatite induced deposition of the treatment layer of the titanium alloy obtained in Example 3 after being immersed in simulated body fluid;
[0034] Figure 6 This is a picture of the in vitro antibacterial plate of titanium alloy obtained in Example 3. DETAILED DESCRIPTION
[0035] In order to make the present invention more clearly understood, preferred embodiments are described in detail below with reference to the accompanying drawings.
[0036] The titanium implants in all the embodiments of the present invention are made of titanium alloy with the grade of TA2.
[0037] The present invention uses the mass of apatite deposited per unit area after immersion in simulated body fluid for 14 days to evaluate the osteoinductive ability of the coating.
[0038] The present invention uses the number of Escherichia coli colonies on an agar plate to evaluate the antibacterial ability of the coating.
[0039] Example 1
[0040] A method for preparing a titanium implant with an osteogenic-antibacterial film layer:
[0041] Step 1: prepare a pretreatment solution, i.e., a solution containing 40 g of NaOH per liter, and stir the solution with deionized water;
[0042] Step 2: prepare a titanium alloy implant surface osteogenic solution, that is, a solution containing 205.71 g of (CH3COO)2Sr per liter of solution, and stir it evenly with deionized water, that is, the solution concentration is 1 M;
[0043] Step 3: prepare an antibacterial solution for the surface of a titanium alloy implant, that is, the solution contains 0.55 g of Zn(NO3)2·6H20 and 11.35 g of dimethylimidazole per liter of solution, and stir the solution evenly with deionized water;
[0044] Step 4: The titanium alloy sample is selected from TA2 alloy, and the selected titanium alloy sample is subjected to a hydrothermal reaction at a high temperature using a pretreatment solution to obtain a titanium implant having a rod-like nanostructure on the surface; during the hydrothermal reaction, the temperature is controlled at 220° C. and the reaction time is 4 hours;
[0045] Step 5: placing the titanium implant obtained in step 4 in an osteogenic solution on the surface of a titanium alloy implant to perform ion exchange to obtain a coating with osteogenic properties; during the ion exchange process, the temperature is controlled at 100° C. and the reaction time is 1 hour;
[0046] Step 6: Place the titanium implant obtained in step 5 in an antibacterial solution to obtain a coating with osteogenic antibacterial properties; during the preparation of the antibacterial coating, the temperature is controlled at 37° C. and the reaction time is 0.5 h.
[0047] The morphology of the coating obtained after the TA2 alloy treatment was immersed in simulated body fluid for 14 days was as follows: Figure 1 ,from Figure 1 It can be seen that the coating is covered with a layer of hydroxyapatite. After the TA2 alloy was treated and tested for antibacterial properties in vitro, the agar plate was Figure 2 ,from Figure 2 It can be seen that there are Escherichia coli colonies on the plate.
[0048] After the TA2 alloy-treated coating was immersed in simulated body fluid for 14 days, the apatite deposition amount was 13.8 mg / cm 2 , the colony count on the agar plate was 57.
[0049] Example 2
[0050] A method for preparing a titanium implant with an osteogenic-antibacterial film layer:
[0051] Step 1: prepare a pretreatment solution, i.e., a solution containing 40 g of NaOH per liter, and stir the solution with deionized water;
[0052] Step 2: prepare a titanium alloy implant surface osteogenic solution, that is, 20.57 g of (CH3COO)2Sr per liter of solution is mixed with deionized water to make a solution and stirred evenly, that is, the solution concentration is 0.1 M;
[0053] Step 3: prepare an antibacterial solution for the surface of a titanium alloy implant, that is, the solution contains 0.55 g of Zn(NO3)2·6H20 and 11.35 g of dimethylimidazole per liter of solution, and stir the solution evenly with deionized water;
[0054] Step 4: The titanium alloy sample is selected from TA2 alloy, and the selected titanium alloy sample is subjected to a hydrothermal reaction at a high temperature using a pretreatment solution to obtain a titanium implant having a rod-like nanostructure on the surface; during the hydrothermal reaction, the temperature is controlled at 220° C. and the reaction time is 6 hours;
[0055] Step 5: placing the titanium implant obtained in step 4 in an osteogenic solution on the surface of a titanium alloy implant to perform ion exchange to obtain a coating with osteogenic properties; during the ion exchange process, the temperature is controlled at 100° C. and the reaction time is 1 hour;
[0056] Step 6: Place the titanium implant obtained in step 5 in an antibacterial solution to obtain a coating with osteogenic antibacterial properties; during the preparation of the antibacterial coating, the temperature is controlled at 37° C. and the reaction time is 1 hour.
[0057] The morphology of the coating obtained after the TA2 alloy treatment was immersed in simulated body fluid for 14 days was as follows: Figure 3 ,from Figure 3 It can be seen that the coating is covered with a layer of hydroxyapatite. After the TA2 alloy was treated and tested for antibacterial properties in vitro, the agar plate was Figure 4 ,from Figure 4 It can be seen that there are Escherichia coli colonies on the plate.
[0058] After the TA2 alloy-treated coating was immersed in simulated body fluid for 14 days, the apatite deposition amount was 8.8 mg / cm 2 , the colony count on the agar plate was 79.
[0059] Example 3
[0060] A method for preparing a titanium implant with an osteogenic-antibacterial film layer:
[0061] Step 1: prepare a pretreatment solution, i.e., a solution containing 40 g of NaOH per liter, and stir the solution with deionized water;
[0062] Step 2: prepare a titanium alloy implant surface osteogenic solution, that is, 2.057 g of (CH3COO)2Sr per liter of solution is mixed with deionized water to make a solution and stirred evenly, that is, the solution concentration is 0.01 M;
[0063] Step 3: prepare an antibacterial solution for the surface of a titanium alloy implant, that is, the solution contains 0.55 g of Zn(NO3)2·6H20 and 11.35 g of dimethylimidazole per liter of solution, and stir the solution evenly with deionized water;
[0064] Step 4: The titanium alloy sample is TA2 alloy, and the selected titanium alloy sample is subjected to a hydrothermal reaction at a high temperature using a pretreatment solution to obtain a titanium implant having a rod-like nanostructure on the surface; during the hydrothermal reaction, the temperature is controlled at 220° C. and the reaction time is 8 hours;
[0065] Step 5: placing the titanium implant obtained in step 4 in an osteogenic solution on the surface of a titanium alloy implant to perform ion exchange to obtain a coating with osteogenic properties; during the ion exchange process, the temperature is controlled at 100° C. and the reaction time is 1 hour;
[0066] Step 6: Place the titanium implant obtained in step 5 in an antibacterial solution to obtain a coating with osteogenic antibacterial properties; during the preparation of the antibacterial coating, the temperature is controlled at 37° C. and the reaction time is 1.5 h.
[0067] The morphology of the coating obtained after the TA2 alloy treatment was immersed in simulated body fluid for 14 days was as follows: Figure 5 ,from Figure 5 It can be seen that the coating is covered with a layer of hydroxyapatite. After the TA2 alloy was treated and tested for antibacterial properties in vitro, the agar plate was Figure 6 ,from Figure 6 It can be seen that there are Escherichia coli colonies on the plate.
[0068] After the TA2 alloy-treated coating was immersed in simulated body fluid for 14 days, the apatite deposition amount was 6.3 mg / cm 2 , the colony count on the agar plate was 45.
[0069] Comparative Example
[0070] A method for preparing a titanium implant:
[0071] Step 1: prepare a pretreatment solution: 40 g of NaOH is contained in each liter of the solution, and the solution is prepared with deionized water and stirred evenly to obtain a hydrothermal reaction solution of the titanium alloy without strontium;
[0072] Step 2: prepare an antibacterial solution for the surface of a titanium alloy implant, that is, the solution contains 0.55 g of Zn(NO3)2·6H20 and 11.35 g of dimethylimidazole per liter of solution, and stir the solution evenly with deionized water;
[0073] Step 3: The titanium alloy sample is TA2 alloy, and the hydrothermal reaction solution of titanium alloy without strontium is used to perform hydrothermal reaction on the selected titanium alloy sample at high temperature. The temperature of the hydrothermal reaction process is controlled at 220°C, and the reaction time is 4 hours. Rod-shaped nanostructures are formed on the surface of the treated titanium alloy sample, which is washed with clean water and dried naturally;
[0074] Step 4: Place the titanium alloy sample obtained in step 3 in an antibacterial solution to obtain a coating with antibacterial properties; during the preparation of the antibacterial coating, the temperature is controlled at 37° C. and the reaction time is 0.5 h.
[0075] After the TA2 alloy-treated coating was immersed in simulated body fluid for 14 days, the apatite deposition amount was 4.1 mg / cm 2 , the colony count on the agar plate was 113.
Claims
1. A method for preparing a titanium implant having an osteogenic-antibacterial film layer, characterized in that: A titanium implant is formed with rod-shaped nanostructures on its surface through a hydrothermal reaction; the titanium implant is then placed in an osteogenic solution, and strontium ions are doped into the nanorods through ion exchange to obtain SrTiO3 nanorods with an osteogenic coating; the SrTiO3 nanorods are placed in an antibacterial solution, and an osteogenic-antibacterial coating is formed on the surface of the SrTiO3 nanorods, thereby obtaining a titanium implant with an osteogenic-antibacterial film layer.
2. The preparation method according to claim 1, characterized in that The hydrothermal reaction is carried out in a NaOH aqueous solution for 4 to 8 hours, and the reaction is rinsed and dried after completion of the reaction.
3. The preparation method according to claim 2, characterized in that: The concentration of the NaOH aqueous solution is 40 g / L.
4. The preparation method according to claim 1, characterized in that: The osteogenic solution is an aqueous solution of (CH3COO)2Sr.
5. The preparation method according to claim 4, characterized in that: The concentration of (CH3COO)2Sr in the osteogenic solution is 2.057-205.710 g / L, and the solvent is deionized water.
6. The preparation method according to claim 1, characterized in that: The titanium implant is placed in an osteogenic solution at a temperature of 100° C. and kept warm for 1 hour.
7. The preparation method according to claim 1, characterized in that: The antibacterial solution is an aqueous solution containing dimethylimidazole and Zn(NO3)2·6H2O.
8. The preparation method according to claim 7, characterized in that: The concentration of dimethylimidazole in the antibacterial solution is 11.35 g / L, the concentration of Zn(NO3)2·6H2O is 0.55 g / L, and the solvent is deionized water.
9. The preparation method according to claim 1, characterized in that: The SrTiO3 nanorods are placed in an antibacterial solution at a temperature of 37°C for 0.5 to 1 hour, and finally rinsed and dried.
10. A titanium implant having an osteogenic-antibacterial film layer prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
A bone tissue implant comprising strontium ions
CN101687062B
Preparation method of strontium-titanate hollow nanorod array
CN102992392A
Novel bone-promoting strontium-containing composite bone repairing material and preparation method and use thereof
CN109091706A
A method for preparing an antibacterial TiO2 and porous carbon nanocomposite material
CN111921514B
Cited By
Near-infrared light response thermal-electric coupling titanium-based implant as well as preparation method and application of near-infrared light response thermal-electric coupling titanium-based implant
CN122075783A